Regulatory Frameworks for Hawala and Other Remittance Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Hawala and other remittance systems have gained attention in recent years with the substantial growth of remittance flows from countries with large migrant labor forces and with increased focus on combating money laundering and the financing of terrorism. The IMF and the World Bank have been researching these systems since 2002 to better understand the interplay of historical, cultural, and economic factors that promote such systems. This book is a survey of regulatory practices and an overview of experiences in different countries, and includes articles on regulatory frameworks in remitting and receiving countries and on the problems that can arise when regulating remittance systems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet